2012
DOI: 10.1063/1.4704696
|View full text |Cite
|
Sign up to set email alerts
|

High electronegativity multi-dipolar electron cyclotron resonance plasma source for etching by negative ions

Abstract: A large area plasma source based on 12 multi-dipolar ECR plasma cells arranged in a 3 × 4 matrix configuration was built and optimized for silicon etching by negative ions. The density ratio of negative ions to electrons has exceeded 300 in Ar/SF6 gas mixture when a magnetic filter was used to reduce the electron temperature to about 1.2 eV. Mass spectrometry and electrostatic probe were used for plasma diagnostics. The new source is free of density jumps and instabilities and shows a very good stability for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Recently, it has been proposed to use both positive and negative-ion beams in space propulsion thrusters 3,4 , instead of positive ion beams alone to reduce neutralization issues. Negative-ion sources are also of interest for microelectronics applications 5,6,7,8,9 . Highly selective, highly anisotropic, notch-free and charge-build-up damage-free etching was evidenced on semiconductors using negative ion beams 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed to use both positive and negative-ion beams in space propulsion thrusters 3,4 , instead of positive ion beams alone to reduce neutralization issues. Negative-ion sources are also of interest for microelectronics applications 5,6,7,8,9 . Highly selective, highly anisotropic, notch-free and charge-build-up damage-free etching was evidenced on semiconductors using negative ion beams 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…In PLD, ions are generally the more energetic species and are responsible for high mobility, sputtering and implantation effects at substrate level. However, only positive ions are usually referred to as ions despite the fact that it is well known that negative ion bombardment is responsible for re-sputtering and damage at the substrate in magnetron sputtering processes [1][2][3], enhancing the formation of metastable structures [4], or producing etching rates similar to positive ions [5,6]. It has been shown that negative ions produced upon RF magnetron sputtering of MgO have KEs ranging up to values higher than 500 eV [7].…”
Section: Introductionmentioning
confidence: 99%
“…The discharge was produced in a cubical vacuum chamber of 40 × 40 × 40 cm 3 , equipped with 12 electron cyclotron resonance (ECR) plasma cells [37] powered by microwaves at 2.45 GHz. A more detailed description is presented elsewhere [38]. The magnetic filter used to reduce the electron temperature was removed for this set of experiments.…”
Section: Methodsmentioning
confidence: 99%